2023
DOI: 10.1002/eqe.3914
|View full text |Cite
|
Sign up to set email alerts
|

Life‐cycle benefits estimation for hybrid seismic‐resistant self‐centering braced frames

Abstract: The hybrid self-centering braced frames (HSBFs) with shape memory alloybased braces (SMABs) and viscous dampers (VDs) are an emerging structural system developed for improving the seismic resilience of traditional braced frames (e.g., buckling restrained braced frames [BRBFs]) and self-centering braced frames (SCBFs) by reducing residual inter-story drifts (RIDs) and floor acceleration responses simultaneously. Nevertheless, the excellent performance of HSBFs is captured by introducing high initial constructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In the elastic analysis of the model, the amplitude of seismic acceleration on the bedrock surface is adjusted to 0.2 g. When the structure is subjected to elastic-dynamic analysis, the seismic propagation directions are all upward along the Z-axis and the vibration direction is the X-direction. In this case, the earthquake record is selected according to China's Code for Seismic Design of Urban Railway Structures (GB 50909-2014), and nine natural earthquake records are selected for elastic time-range calculations [29][30][31][32][33], which comprise three low-frequency earthquake records (L-1~3), three medium-frequency earthquake records (I-1~3), and three high-frequency earthquake records (H-1~3) [34][35][36]; the information of the earthquake records is shown in Table 4. The time-range curves and Fourier spectra are shown in Figure 4.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…In the elastic analysis of the model, the amplitude of seismic acceleration on the bedrock surface is adjusted to 0.2 g. When the structure is subjected to elastic-dynamic analysis, the seismic propagation directions are all upward along the Z-axis and the vibration direction is the X-direction. In this case, the earthquake record is selected according to China's Code for Seismic Design of Urban Railway Structures (GB 50909-2014), and nine natural earthquake records are selected for elastic time-range calculations [29][30][31][32][33], which comprise three low-frequency earthquake records (L-1~3), three medium-frequency earthquake records (I-1~3), and three high-frequency earthquake records (H-1~3) [34][35][36]; the information of the earthquake records is shown in Table 4. The time-range curves and Fourier spectra are shown in Figure 4.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…Both studies concluded that these bracing systems have promising potential for enhancing the seismic resilience of buildings. Although the cost of SMA components is higher than that of traditional components, the latest investigations confirmed the life-cycle span benefits of SMA-based braces with reduced initial costs [12]. Alternative configurations for SMA-based superelasticity-assisted sliders (SSS) were proposed by Narjabadifam et al [13].…”
Section: Introductionmentioning
confidence: 99%